PEMBERDAYAAN DAN PENGEMBANGAN WIRAUSAHA PEREMPUAN MUDA PADA RUMAH TANGGA MISKIN DI KECAMATAN MEDAN DELI KOTA MEDAN - Damai Yona Nainggolan (Universitas Medan Area, 2014)
Women's poverty issues become increasingly complex because it turns out women's poverty is not only caused by the limitation of access to economic resources. There are structural problems with the cause factor and not a single constraint, tend to vary according to the conditions of political, economic and social in their neighborhood. The existence of gender inequality in various aspects of life also worsening conditions of poverty on women.This is because the dual role that they have to run, on the one hand as a housekeeper and the other side as the breadwinner of the family. This research is quantitative descriptive. The results showed a young woman from RTM have education good enough, where the majority of the already educated junior high scholl and senior high school, although there is still educated to elementary school or never attended school because of limited funds bench, have low skills because of the presence of the non formal education yet or training undertaken, have a desire to seek self help especially in the field of trade and agriculture, has limited capital to be able to start a business for that initial funds needed to encourage them to start trying, have the potential to alleviate themselves from poverty if given help to seek.